Development of the sustainability index for the ready-made garments sector in Bangladesh - Md Abdus Salam; Kalayanee Senasu (Business: Theory and Practice, 2019)
The aim of this research is to develop a simple and easily useable scale to assess sustainable development in the ready-made garments (RMG) sector in Bangladesh. A framework has been proposed where sustainable development dimensions, sub-dimensions (or variables) under dimensions, and items under sub-dimensions, are developed through an extensive literature review. This framework serves as the base for index development in this study. The proposed framework comes in the form of a questionnaire. After receiving satisfactory results from the pilot study, further information was gathered from the Tier 1 RMG factories in Bangladesh using the proposed questionnaire. Excluding the incomplete responses, a total of 238 responses were considered for further analysis. Following this, the collected data were passed through a number of statistical processes including item-total correlation and CFA (Confirmatory Factor Analysis). After rigorous analysis, only 30 items were shown to be model fit according to the proposed second-order sustainability index model. Finally, the results of factor loading showed that dimensions load very well on the proposed framework. Therefore, this study culminated in developing a 30-item valid and reliable sustainability index for three dimensions: economic, environmental, and social, for the Bangladeshi RMG sector.